2004
DOI: 10.1075/japc.14.2.04cha
|View full text |Cite
|
Sign up to set email alerts
|

Culture and rapport promotion in service encounters

Abstract: The present study aimed at investigating possible cultural effects on the perceived importance of interactional concerns in service encounters. Individual values were examined to establish an explanatory framework for any effects that might emerge. Hong Kong Chinese and Filipinos participated in the present study by rating the importance of 12 interactional concerns in five hypothetical scenarios involving service provision. “Rapport promotion” was the only consistent factor of interactional concerns to emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Gonzalez, 2002, 2005;Knafo and Sagiv, 2004;Poling et al, 2004;Koivula and Verkasalo, 2006); satisfaction from the provision of various services (e.g. Chan et al, 2004;Fegg et al, 2005); attitude towards violence, war and fear (e.g. Konty et al, 2004;Cohrs et al, 2005a,b); attitude towards various types of risk (e.g.…”
Section: Values Theory and The Portrait Value Questionnairementioning
confidence: 98%
“…Gonzalez, 2002, 2005;Knafo and Sagiv, 2004;Poling et al, 2004;Koivula and Verkasalo, 2006); satisfaction from the provision of various services (e.g. Chan et al, 2004;Fegg et al, 2005); attitude towards violence, war and fear (e.g. Konty et al, 2004;Cohrs et al, 2005a,b); attitude towards various types of risk (e.g.…”
Section: Values Theory and The Portrait Value Questionnairementioning
confidence: 98%
“…Recognizing the imperative role of culture in social interactions in human societies, culture must have meaningful associations with initiating and building rapport. Yet, despite that decades of research have identified specific behaviors and components of rapport (described above), with few exceptions (Bernieri & Gillis, 1995; Chan et al, 2004; Spencer-Oatey, 2000, 2005), there is a surprising dearth of cross-cultural comparative research in this area, and none in investigative contexts. Cultural differences in conceptualizing rapport are likely, for several reasons.…”
Section: Classic Research On the Nature And Function Of Rapportmentioning
confidence: 99%
“…Ros et al, 1999;Munene et al, 2000;Gonzalez, 2002, 2005;Poling et al, 2004;Knafo and Sagiv, 2004;Koivula and Verkasalo, 2006); service satisfaction (e.g. Chan et al, 2004;Fegg et al, 2005); attitude towards violence, war and fear (e.g. Boehnke and Schwartz, 1997;Konty et al, 2004;; and attitude towards various types of risk (e.g.…”
Section: Portrait Value Questionnaire's Usefulnessmentioning
confidence: 99%